Chondrosarcoma maxillae – a case report - Zielińska-Kaźmierska, Bogna; Grodecka, Joanna; Neskoromna, Aneta (Contemporary Oncology/Współczesna Onkologia, 2005)
Chondrosarcoma is a second frequently bone tumor. It may appear in different places but most frequently in illiac bone, chest and shoulder blade. In facial region it takes place more rare. Clinical reports of Chondrosarcoma s at lower and upper jaws are not numerous describe in literature. Chondrosarcoma has various character of growth which depending on the degree of histological malignancy. It rarely gives metastases at the first degree of malignancy or grows more dynamic causing pain symptoms. Such tumor gives often early distant metastases (at third degree of histological malignancy). Total tumor resection with large margin of healthy tissues is preferable treatment method. Adiuvant radiotherapy can significant delay of a local reissue in cases in which tumor localization unable total resection. At third degree of malignancy an adiuvant chemotherapy can be used. Authors are present a case report 21-years-old patient with Chondrosarcoma of maxilla. We are describe hidden period of disease, treatment methods which were unsuccessfully. Unificated methods of treatment those tumors are unknown in world literature.